Transforming Corn Stalks into Sustainable Block Boards for Durable Children's Toys: A Material Science Perspective Linked to Sustainable Development Goals - Puspita Nurlilasari; Nurvirzy Muflih Attallah; Andry Masri (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This paper presents a comprehensive study on the transformation of corn stalks, an abundant agricultural waste, into structurally reliable block boards with high bending strength suitable for children’s toys. The innovation leverages physical principles of matter states, fiber mechanics, and sustainable design thinking inspired by Andry Masri’s creative-industrial research. The resulting material meets key performance indicators in bending, elasticity, water resistance, and cost competitiveness. Furthermore, this study frames the material’s development and application within the United Nations Sustainable Development Goals .SDGs., particularly SDG 3, 9, 12, 13, and 15.